Suppression of autophagy and antigen presentation by Mycobacterium tuberculosis PE_PGRS47 - Saini, Neeraj K. (Nat Microbiol, 2016)
Suppression of major histocompatibility complex (MHC) class II antigen presentation is believed to be among the major mechanisms used by Mycobacterium tuberculosis to escape protective host immune responses. Through a genome-wide screen for the genetic loci of M. tuberculosis that inhibit MHC class II-restricted antigen presentation by mycobacteria-infected dendritic cells, we identified the PE_PGRS47 protein as one of the responsible factors. Targeted disruption of the PE_PGRS47 (Rv2741) gene led to attenuated growth of M. tuberculosis in vitro and in vivo, and a PE_PGRS47 mutant showed enhanced MHC class II-restricted antigen presentation during in vivo infection of mice. Analysis of the effects of deletion or over-expression of PE_PGRS47 implicated this protein in the inhibition of autophagy in infected host phagocytes. Our findings identify PE_PGRS47 as a functionally relevant, non-redundant bacterial factor in the modulation of innate and adaptive immunity by M. tuberculosis, suggesting strategies for improving antigen presentation and the generation of protective immunity during vaccination or infection.